World General Knowledge - Dogar, Tariq Mehmood (Lahore Dogarsons, 1996)
It is prepared for the CSS, PCS, Police, Customs, Banks, Doctors' Test, Engineers' Test and other Civil and Military Competitive Examinations and Interviews.
Including everyday Science, Islamyat and Pakistan Studies.
Keywords: World General Knowledge -- CSS, PCS, Police, Customs, Banks -- Doctors' Test, Engineers' Test and other Civil and Military Competitive Examinations -- Interviews